PERSEPSI KUALITAS PELAYANAN BUS TRANS JATIM KORIDOR I (SIDOARJO-SURABAYA-GRESIK) SEBAGAI TRANSPORTASI PUBLIK DI JAWA TIMUR - Siti Kasiani; Agus Widiyarta (LPPM Universitas Abdurrab, 2023)
In the process of economic and social development, transportation has an important role. Along with population growth which continues to increase, the need for transportation facilities is also increasing. In Indonesia, especially in East Java, private vehicles, especially motorbikes, are the most widely used mode of transportation. Facing the problems of congestion, accident rates, and gas emissions from motorized vehicles, the East Java Provincial government is trying to improve the quality of public transportation through the presence of the Bus Trans Jatim. This was greeted with high public interest in using the service, which had an impact on the accumulation of passengers at bus stops. In addition, there are access problems for persons with disabilities due to the steep slope of the ramp. This study aims to examine the perceptions of the public using the Bus Trans Jatim service Corridor I (Sidoarjo-Surabaya-Gresik). Quantitative method with descriptive approach is used in this research, with 100 respondents as sample. Public perception is measured using the dimensions of service quality according to the Parasuraman model, V.A. Zaithaml, and Leonard L. Berry. The results showed that the user's perceptions on the tangibles, reliability, assurance, and empathy dimensions were categorized as satisfied, while the responsiveness dimension was categorized as very satisfied. Overall, the user's perception of the Trans Jatim Bus Corridor I service can be concluded as being satisfied with a percentage score of 85%.